Research Review on Wear Resistance and Lubricity of Diamond-Like Carbon Films by Magnetron Sputtering - WANG Jiangang, FAN Yuxing, ZHANG Xin, WANG Yujiang, LUO Wei, WANG Lei, WANG Jingjing (Cailiao Baohu)
Diamond-like carbon (DLC) films have drawn considerable attention in various fields due to their excellent lubricating and wearresistant properties.This paper systematically reviewed the research progress of magnetron sputtering technology in DLC film preparation， with emphasis on the regulating mechanisms of process parameters and elemental doping on film performance.Firstly， the effects of key parameters including gas flow ratio， bias voltage and current on the microstructure and tribological properties of DLC films were analyzed: optimizing gas ratios (e.g.， Ar/CH4) could regulate the sp2/sp3 bond ratio to reduce the friction coefficient； bias voltage control could balance film hardness and surface defects； current adjustment directly affected the ion flux and sp3 bond stability.Secondly， the doping mechanisms of non-metal(Si， N， F) and metal (Cr， Ti) elements were summarized: Si doping enhanced high-temperature stability and reduced residual stress； N doping promoted graphitic structure formation； F doping passivated surface dangling bonds through C-F bonds； while Cr and Ti incorporation inhibited oxidation through carbide phases and optimized mechanical properties.Finally， the development prospects of DLC film technology were prospected.